Penerapan Pendekatan Ekspositori pada Penulisan Naskah Video Feature "Buatan yang Menjadi Tangan Kehidupan" - Viola Putri Ningtyas; Kokom Komariah; Nurmaya Prahatmaja (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2026)
As feature videos have increasingly become a medium for communicating factual information, scriptwriting plays a crucial role in organizing narratives that are coherent, informative, and meaningful. Through an expository approach, scriptwriters are able to integrate narration, factual data, interviews, and supporting visuals into a structured audiovisual narrative. This study aims to explain the application of the expository approach in Act I: Birth, Act II: Growth, and Act III: Survival in the scriptwriting process of the feature video Buatan yang Menjadi Tangan Kehidupan (The Artificial That Became the Hand of Life). The study employed a practice-based creation method consisting of pre-production, production, and post-production stages, with the script developed using an expository approach within a three-act narrative structure. The findings indicate that the expository approach in Act I establishes contextual understanding by presenting information progressively from broad issues to the main subject; Act II develops the discussion by logically connecting the history, development, and functions of Situ Cileunca; and Act III integrates research findings, interviews, and reflective narration to strengthen the central message regarding the importance of preserving water quality. The implementation of the expository approach resulted in a feature video script that presents information systematically, factually, and communicatively while enabling audiences to develop a comprehensive understanding of water as a source of life. These findings contribute to scriptwriting practices by demonstrating how the expository approach can be systematically applied to produce coherent and informative feature video scripts.